The Alchemist A Fable About Following Your Dream - Paulo Coelho (San Francisco HarperOne, 2014)
A special 25th anniversary edition of the extraordinary international bestseller, including a new Foreword by Paulo Coelho.
This book is an English version of O Alquimista, the Portuguese original edition, published in Brazil by Editora Rocco Ltd. (Rio de Janeiro). Copyright 1988 by Paulo Coelho. Previous paperback editions were published in 1994 and 1998 by HarperOne, a division of HarperCollins Publishers. A HarperFlamingo edition was published in 1998. A previous HarperPerennial paperback edition was published in 1998 ... English version copyright 1993 by Paulo Coelho and Alan R. Clarke. Updated introduction copyright 2014 by HarperCollins Publishers"--Title page verso.
Keywords: General; BODY, MIND & SPIRIT -- Inspiration & Personal Growth; Alchemists; Alchemy; Quests (Expeditions); Self-realization; Shepherds; Young men; Body, Mind & Spirit -- Inspiration & Personal Growth; Spain -- Andalusia; Electronic books; Fiction; Fables